Influence of silica resource from rice husk on structure of HZSM-5 zeolite - Hoai Nam, Le Thi; Thanh Loan, Nguyen Thi (Vietnam Journal of Chemistry, 2014)
HZSM-5 zeolites were successfully synthesized by hydrothermal treament using silica  from rice husk and glasses water. The samples were characterized by XRD, IR, SEM, TEM, BET and 27Al-NMR methods. Characterization results revealed that HZSM-5 material synthesized from rice husk silica has crystallinity and acidity as high as HZSM-5 sample synthesized from glasses water. HZSM-5 material synthesized from rice husk silica not only has  the conventional pores system as shown structure of HZSM-5 sample synthesized from glasses water, but also has mesoporous system with kinetic diameter in range of 10-50 nm. This multi-porous system is expected to increase significantly the catalytic activity of synthesized material in the reactions with the present of large molecules . Keywords: Rice husk silica, ZSM-5, multi-porous system